Fitness cost implications of phiC31-mediated site-specific integrations in target-site strains of the Mexican fruit fly, Anastrepha ludens (Diptera: Tephritidae) - Meza, José S.; Díaz-Fleischer, Francisco; Sánchez-Velásquez, Lázaro R.; Zepeda-Cisneros, Cristina Silvia; Handler, Alfred M.; Schetelig, Marc F.; Justus Liebig University Giessen (My University, 2014)
Site-specific recombination technologies are powerful new tools for the manipulation of genomic DNA in insects that can improve transgenesis strategies such as targeting transgene insertions, allowing transgene cassette exchange and DNA mobilization for transgene stabilization. However, understanding the fitness cost implications of these manipulations for transgenic strain applications is critical. In this study independent piggyBac-mediated attP target-sites marked with DsRed were created in several genomic positions in the Mexican fruit fly, Anastrepha ludens. Two of these strains, one having an autosomal (attP_F7) and the other a Y-linked (attP_2-M6y) integration, exhibited fitness parameters (dynamic demography and sexual competitiveness) similar to wild type flies. These strains were thus selected for targeted insertion using, for the first time in mexfly, the phiC31-integrase recombination system to insert an additional EGFP-marked transgene to determine its effect on host strain fitness. Fitness tests showed that the integration event in the int_2-M6y recombinant strain had no significant effect, while the int_F7 recombinant strain exhibited significantly lower fitness relative to the original attP_F7 target-site host strain. These results indicate that while targeted transgene integrations can be achieved without an additional fitness cost, at some genomic positions insertion of additional DNA into a previously integrated transgene can have a significant negative effect. Thus, for targeted transgene insertions fitness costs must be evaluated both previous to and subsequent to new site-specific insertions in the target-site strain.
Keywords: ddc:630